Change in walking cadence as a digital outcome measure of clinically meaningful improvement in gait speed and 6-minute walk test distance after a mobility intervention in older adults - Daniel S. Rubin; Nancy W. Glynn; Marcin Straczkiewicz; Margaret K. Danilovich; Christopher Sciamanna; Jennifer S. Brach (PLoS ONE, 2026)
Mobility assessments are essential for evaluating baseline function and monitoring responses to interventions in older adults. Usual-pace gait speed and the 6-minute walk test (6MWT) are widely used and reproducible measures with established minimum clinically important differences (MCIDs) to distinguish responders from non-responders. However, both require in-person administration, limiting their scalability in clinical trials and population-based studies. Walking cadence, a measure of walking intensity that can be captured digitally, may offer a scalable alternative for identifying responders versus non-responders to mobility interventions. We conducted a secondary analysis of the prospective Program to Improve Mobility in Aging (PRIMA) cohort trial to evaluate whether changes in walking cadence after a walking intervention could identify responders versus non-responders. Cadence was measured during usual-pace gait speed testing and the 6MWT, and logistic regression models assessed its ability to predict achievement of MCIDs for gait speed (>0.1 m/s) and 6MWT distance (>30 m) in older adults. Data from 213 participants were analyzed. Change in median walking cadence predicted improvement in usual-pace gait speed with an area under the curve (AUC) of 0.90 (95% CI: 0.85–0.94). The Youden Index identified an increase of ≥3 steps/min as the optimal threshold (sensitivity 0.81; specificity 0.88). For predicting improvement in 6MWT distance, the AUC was 0.80 (95% CI: 0.74–0.86), with the same ≥3 steps/min threshold (sensitivity 0.75; specificity 0.77). These findings suggest that changes in walking cadence during usual-pace gait and the 6MWT may serve as a digitally measurable outcome to identify responders to mobility interventions. Further research is warranted to validate these findings in remote and real-world applications.